Growth, Yield and Nutrient Uptake of Direct Seeded Rice as Affected by Nitrogen and Phosphorus Application - Abdul Rahman, Rafeah (1996)
Pot and field trials using rice varieties IR 72, MR 84 and MR 142 were conducted to determine the effects of N and P rate on growth, yield, yield components and nutrient uptake of direct seeded rice. The experiments were carried out in a Randomised Complete Block design with four replicates, for the pot trial and three replicates for the field trial. Results from the pot trial indicated that higher N rate increased plant height, tiller number, total dry matter (TDM) and leaf area of direct seeded rice at the different growth stages by 5-8%, 42-43 %, 30-40%, 58-60% respectively. Varietal differences in plant height, tiller number and TDM were related to differences in growth rate and maturation period. Interaction effects of variety x N rate were observed on grain yield and yield components. Higher N increased grain yield of IR 72, MR 142 and MR 84 by 49%, 43% and 26% respectively. Total N, P and K tissue content was increased by 35- 68% with higher N application. At early stages of growth, varietal differences mainly involved P and K content but at heading included N, P and K content. There was however, no significant effect of P rate on all the parameters measured.